Differences in Adherence and Non-Adherence Behaviour Patterns to Inhaler Devices Between COPD and Asthma Patients. (2nd September 2016) - Plaza, Vicente; López-Viña, Antolín; Entrenas, Luis Manuel; Fernández-Rodríguez, Concepción; Melero, Carlos; Pérez-Llano, Luis; Gutiérrez-Pereyra, Fernando; Tarragona, Eduard; Palomino, Rosa; Cosio, Borja G.
Abstract: Differences between COPD and asthma may also differentially affect adherence to inhaled drugs in each disease. We aimed to determine differences in behaviour patterns of adherence and non-adherence to inhaled therapy between patients with COPD and patients with asthma using the Test of Adherence to Inhalers (TAI) questionnaire. A total of 910 patients (55% with asthma, 45% with COPD) participated in a cross-sectional multicentre study. Data recorded included sociodemographics, education level, asthma or COPD history, TAI score, the Asthma Control Test (ACT), the COPD Assessment Test (CAT) and spirometry. Asthma patients were statistically significant less adherents, 140 (28%) vs. 201 (49%), and the pattern of non-adherence was more frequently erratic (66.8% vs. 47.8%) and deliberate (47.2% vs. 34.1%) than COPD patients; however unwitting non-adherence was more frequently observed in COPD group (31.2% vs. 22.8%). Moreover, taking together all sample studied, only being younger than 50 years of age (OR 1.88 [95% CI: 1.26–2.81]) and active working status (OR 1.45 [95% CI: 1.00–2.09]) were risk factors for non-adherence in the multivariate analysis, while having asthma remained in the limits of the significance (OR 1.44 [95%CI: 0.97–2.14]). Even though non-adherence to inhalers is more frequently observed in asthma than in COPD patients and exhibited a different non-adherence patterns, these differences are more likely to be related to sociodemographic characteristics. However, differences in non-adherence patterns should be considered when designing specific education programmes tailored to each disease.